2000
DOI: 10.1034/j.1600-0501.2000.011005430.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases‐1, matrix metalloproteinases‐1 and ‐8, and collagenase activity levels in peri‐implant crevicular fluid after implantation

Abstract: The integrity of connective tissues surrounding dental implants may be influenced by a balance between matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs). The purpose of this study was to provide an overall assessment of TIMP-1, MMP-1 and -8 levels as well as collagenase activities during the wound healing process after implantation and in peri-implantitis lesions. Peri-implant crevicular fluid (PICF) was sampled with sterile paper strips from 10 osseointegrated implants of 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 36 publications
6
61
0
Order By: Relevance
“…Besides PGE 2 , MMP-8 is also shown to exhibit higher levels in periimplant inflammatory processes on comparing with healthy implants. [27][28][29]38,39 Incompatibly, Aboyoussef et al had not observed differences between the healthy state and early periimplantitis regarding MMP levels. However, the investigators claimed that a more critical analysis of MMP levels should be carried out using a specific assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides PGE 2 , MMP-8 is also shown to exhibit higher levels in periimplant inflammatory processes on comparing with healthy implants. [27][28][29]38,39 Incompatibly, Aboyoussef et al had not observed differences between the healthy state and early periimplantitis regarding MMP levels. However, the investigators claimed that a more critical analysis of MMP levels should be carried out using a specific assay.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Elevated levels of MMP-8 in diseased PICF and the existence of a strong correlation between MMP-8 levels and GI scores have been reported in diseased periimplantitis sites. [27][28][29] However, no studies have focused on the prospective detection of PGE 2 together with MMP-8 in PICF after implantation. The purpose of the present investigation was to detect the levels of PGE 2 and MMP-8 in PICF longitudinally up to 18 months after osseointegration and loading, to assess the interaction between these mediators and clinical parameters, and also to assess whether the detection of these mediators in PICF might be useful in diagnosing early tissue breakdown.…”
mentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) consistently have been implicated in extracellular matrix degradation during chronic inflammation of periodontitis, particularly MMP‐8 (neutrophil collagenase) . Studies have detected MMP‐8 in saliva and GCF of periodontitis patients and in PICF of PIP patients suggestive that MMP‐8 levels may be useful for diagnostic monitoring of the connective tissue destruction phase of peri‐implant disease. MMP‐8, including targeting its active form, has been reported to represent a valuable target for chairside point‐of‐care testing of oral fluids related to detection of periodontitis, and more recently in PIP; albeit active MMP‐8’s ability to affect treatment decision‐making remains to be fully elucidated and implemented within the global dental profession.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PI and GI, GCF/PICF samples were collected from four sites per tooth or implant and were repeated twice per site (e.g., mesial, distal, buccal, and lingual sites). Strips assigned for enzyme-linked immunosorbent assay (ELISA) were placed in an enzyme reaction buffer containing 50 mM Tris-HCl, 0.2 M NaCl, and 5 mM CaCl 2 at pH 7.5 and centrifuged at 13,000 × g for 10 minutes; the supernatant was kept frozen at −80°C 30. Strips assigned for high performance liquid chromatography (HPLC) assay were placed into a sterile vial with no buffer and kept at −20°C 31…”
Section: Methodsmentioning
confidence: 99%